Identifikasi Keragaman Gen FASN (Fatty Acid Synthase) sebagai Kandidat Gen Kualitas Daging pada Sapi Pasundan Betina - Putri, Verlia Dwi; Mayasari, Novi; Hernaman, Iman; Ramdani, Diky; Sulastri, Erni; Hilmia, Nena (Unpad Press, 2025)
Pasundan cattle are one of Indonesia’s local cattle thathave the potential to be developed, especially in terms of meatquality. Meat quality is strongly influenced by fatty acidcomposition, which is closely related to gene regulation. This studyaims to identify the diversity of the FASN (fatty acid synthase) geneas a candidate gene for meat quality in female Pasundan cattle. Thisstudy used an experimental descriptive method with 25 DNAsamples of female Pasundan cattle with an age range of 1,5-2 years.DNA amplification using PCR was perfomed with specific primersdesigned with NCBI Primer Blast, flanking the target gene along560 bp. The analysis was followed by PCR-RFLP (RestrictionFragment Length Polymorphism) method using MscI enzyme todetect single nucleotide polymorphism (SNP) g.17924 A>G in exon39 and confirm the target mutation using direct sequencingmethod. The results showed only one genotype, the GG genotype(100%), with a G allele frequency of 1.00. Based on these results, itcan be concluded that the FASN gene mutation g.17924 A>Gmutation in Pasundan cattle is monomorphic. SNP g.17924 A>G inthe FASN gene has the potential to affect the fatty acid compositionof Pasundan female beef